Sodium metabisulfite as a cytotoxic food additive induces apoptosis in HFFF2 cells. (1st October 2021) - Alimohammadi, Afshin; Moosavy, Mir-Hassan; Amin Doustvandi, Mohammad; Baradaran, Behzad; Amini, Mohammad; Mokhtarzadeh, Ahad; de la Guardia, Miguel
Highlights: Cytotoxic effects of SMB were investigated on HFFF2 cells. SMB reduced cell viability and induced apoptosis. SMB modulated the expression of genes involved in apoptosis pathways. This food additive increased ROS levels and activated autophagy. Abstract: Sodium metabisulfite (SMB), an antioxidant agent, is extensively used as a preservative in food industry. The current study was aimed to clarify its potential toxic effects on human fetal foreskin fibroblasts (HFFF2) cells, in vitro. Subsequently, MTT results illustrated that exposure to SMB significantly ( p < 0.0001 ) decreased HFFF2 cell viability in a dose-dependent manner, and the concentration of 25 μM reduced cell survival rates to 50% as the half-maximal inhibitory concentration of SMB. It was further shown that SMB exerted this cytotoxic effect on HFFF2 cells through apoptosis induction. qRT-PCR and western blotting results showed that treatment of HFFF2 cells with this food additive led to significant upregulation of Bax, caspase 8, and caspase 9 pro-apoptotic genes and downregulation of Bcl-2 expression as a pro-survival agent. Furthermore, SMB remarkably increased caspase 3 levels and promoted its activation through cleavage in treated cells. Besides, exposure to SMB increased ROS levels and activated autophagy in treated cells, which are considered as the other indicators for cell damage. Taken together, our findings suggested that SMB could exert remarkable toxic effects on human normal cells through multiple mechanisms,  including apoptosis activation, and its widespread usage in food safety should be reconsidered.